2015
DOI: 10.17311/sciintl.2015.48.57
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Sequestration of CO2 Using Carbonic Anhydrase from Calcite Encrust Forming Marine Actinomycetes

Abstract: Background: CO 2 in the environment has been a burning issue and aggravated the threats of global warming. Various strategies are being used to decrease the level of releasing CO 2 . Biosequestration is a one of the available nontoxic, robust and eco-friendly approaches but still less evaluated. This study reports the role of microbial Carbonic Anhydrase (CA) in the formation of calcite by utilizing CO 2 . Methods: The marine Nocardiopsis lucentensis was studied for intracellular microbial CA. Isolate grown op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Using p-NPA as a colour indicator during its hydrolysis, we have determined that all isolated marine strains could exhibit carbonic anhydrase activity. This later has been found to have a great potential for production of carbonates [20,21]. Carbonic anhydrase is a major enzyme that plays an important role in carbon concentrating mechanism and sequestration of CO 2 into calcium carbonate [29].…”
Section: Metabolic Pathways Involved In Biomineralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using p-NPA as a colour indicator during its hydrolysis, we have determined that all isolated marine strains could exhibit carbonic anhydrase activity. This later has been found to have a great potential for production of carbonates [20,21]. Carbonic anhydrase is a major enzyme that plays an important role in carbon concentrating mechanism and sequestration of CO 2 into calcium carbonate [29].…”
Section: Metabolic Pathways Involved In Biomineralizationmentioning
confidence: 99%
“…À and H + , which under certain conditions can capture atmospheric CO 2 [20,21]. In the context of coastal protection, our purpose is to design ecomaterials that mimic naturally-formed rock structures at the seaside and to accelerate their growth kinetics by coupling electrochemical processes with microbial mechanisms of biomineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria produce enzymes belonging to three distinct classes of CA, α, β, and γ, which have no significant sequence or structural identity [69]. CA are major enzymes that play a significant role in the carbon-concentrating mechanism and sequestration of CO 2 into calcium carbonate [70][71][72]. It has been reported that this enzyme alone can accelerate the rate of CaCO 3 formation by releasing carbonate and bicarbonate ions in large quantities [73,74].…”
Section: Metabolic Characterisation Of the Biocalcifying Bacteriamentioning
confidence: 99%
“…To remove CO 2 , MICP that converts CO 2 into carbonate minerals has been shown to be an effective method (Anbu et al, 2016). As a safe and environment-friendly technique, carbonicanhydrase-enzyme mediated MICP catalyzes reversible hydration of CO 2 to formations of bicarbonates and calcite crystals (Liu et al, 2005;Kim et al, 2012). The carbonic anhydrase enzyme when purified deposits 15 times more carbonates than its crude counterpart (i.e., cells washed and resuspended in lysis buffer) (Ramanan et al, 2009).…”
Section: Removal Via Microorganismsmentioning
confidence: 99%